CLINICAL IMPORTANCE OF DEFINITION OF SINGLE NUCLEOTIC POLYMORPHISMS IN PATIENTS WITH BREAST CANCER (LITERATURE REVIEW) - Benberin V. V.; Shanazarov N. A.; Seidalin N. K.; Lisovska N. Y.; Voshchenkova T. A.; Yermakhanova G. A. (Scientific Journal of Pedagogy and Economics, 2019)
Purpose of the review: The study of literature data relating to the replacement of nucleotides in DNA with the risk of development, course and prognosis of breast cancer. Materials and methods. A literature review was conducted in electronic databases included in PubMed/Medline, The Cochrane Library. The depth of search was 10 years. Results. The data on the role of single nucleotide polymorphisms in the development, course, prognosis and response to treatment for breast cancer in individual populations was studied. The research results show that the replacement of nucleotides in DNA underlies the differences in susceptibility to the development of diseases, the effectiveness of the action of medicines. Conclusion. The determination of single nucleotide polymorphisms can reveal a hereditary predisposition to various multifactorial diseases (including cancer), and to predict individual sensitivity to pharmacological medicines. This can help physicians choose the most effective treatment for breast cancer patients.